2022
DOI: 10.5603/gp.a2022.0041
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve analysis of single-site incision laparoscopic adnexal surgery performed by a single surgeon

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited.Articles in "Ginekologia Polska" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Bonollo et al ( 5 ) also reported that laparoendoscopic single-site surgery does not seem to demonstrate a clear superiority over MPLS, except for better cosmetic results in benign gynecological surgery. Yi ( 4 ) reported that single-site incision laparoscopic surgery for adnexal surgery is a safe technique. However, a certain training period for learning the technique is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bonollo et al ( 5 ) also reported that laparoendoscopic single-site surgery does not seem to demonstrate a clear superiority over MPLS, except for better cosmetic results in benign gynecological surgery. Yi ( 4 ) reported that single-site incision laparoscopic surgery for adnexal surgery is a safe technique. However, a certain training period for learning the technique is required.…”
Section: Discussionmentioning
confidence: 99%
“…Single-port laparoscopic surgery (SPLS) has become a common procedure for treating benign ovarian tumors ( 2 ). Studies by Capozzi et al ( 3 ) and Yi ( 4 ) have shown that single-site surgery seems to be a feasible and safe gynecological procedure for women with benign ovarian tumors. However, Bonollo et al ( 5 ) have reported that current evidence does not seem to demonstrate a clear superiority of laparoendoscopic single-site surgery over multiport laparoscopic surgery (MPLS), except for producing cosmetic results in benign gynecological surgery.…”
Section: Introductionmentioning
confidence: 99%